Transformation of the Agricultural Industry Based on Thayyiban Halalan Principles: Strengthening Regulations and Technological Innovation in Facing Global Halal Trends - Indi Millatul Maula; Widya Widya (Return : Study of Management, Economic and Bussines, 2026)
The halal industry has now shifted from simply fulfilling religious obligations to global quality standards that include strategic sectors such as agriculture. This research aims to analyze potential, identify upstream-downstream technical challenges, and evaluate the implementation of halal industry development in the agricultural sector in Indonesia. The method used is qualitative descriptive with a case study approach on the Halal Agribusiness Area. Data was collected through literature studies on national regulations, institutional reports in 2023, and scientific literature related to halal supply chains. The results of the study show that Indonesia has great potential supported by the contribution of the agricultural sector to GDP of 13.5% and a significant increase in halal certification. However, the fundamental challenges are still found in the low halal literacy of farmers, the lack of specific regulations for agricultural inputs such as fertilizers and seeds, and the low allocation of halal research budgets which only reaches 5%. A case study in East Lombok proves that the integration of halal standards with organic farming systems and traceability can increase the economic value of products by 20-25%. The conclusion of this study emphasizes that the acceleration of the halal agriculture industry requires regulatory synergy, strengthening halal laboratory infrastructure, and replicating the community-based agribusiness area model to increase global competitiveness in accordance with the vision of Golden Indonesia 2045. These findings imply that evidence-based policy interventions particularly in halal regulatory harmonization, halal infrastructure development, and farmer capacity building.